2014
DOI: 10.1038/srep07164
|View full text |Cite
|
Sign up to set email alerts
|

pentahexoctite: A new two-dimensional allotrope of carbon

Abstract: The ability of carbon to exist in many forms across dimensions has spawned search in exploring newer allotropes consisting of either, different networks of polygons or rings. While research on various 3D phases of carbon has been extensive, 2D allotropes formed from stable rings are yet to be unearthed. Here, we report a new sp2 hybridized two-dimensional allotrope consisting of continuous 5-6-8 rings of carbon atoms, named as “pentahexoctite”. The absence of unstable modes in the phonon spectra ensures the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 46 publications
4
61
0
Order By: Relevance
“…The corresponding lattice parameters are prvodied in Table 1. The a-, b-, and d-phases are the rst time proposed carbon allotropes while the g-and 3-phases correspond to the previously reported ones by Mandal et al 31 and Sharma et al, 30 respectively. Referring to the lowest energy a-phographene, the b-, g-, d-, and 3-phases are calculated on PBE-level to be 7, 50, 64, and 157 meV per atom higher in total energy, respectively.…”
Section: Geometrical Conguration and Stabilitysupporting
confidence: 84%
See 1 more Smart Citation
“…The corresponding lattice parameters are prvodied in Table 1. The a-, b-, and d-phases are the rst time proposed carbon allotropes while the g-and 3-phases correspond to the previously reported ones by Mandal et al 31 and Sharma et al, 30 respectively. Referring to the lowest energy a-phographene, the b-, g-, d-, and 3-phases are calculated on PBE-level to be 7, 50, 64, and 157 meV per atom higher in total energy, respectively.…”
Section: Geometrical Conguration and Stabilitysupporting
confidence: 84%
“…In addition to the geometrical stability of the 5-7 polygons, the 5-8 polygons are actually also stable conguration as evidenced in the experimental studies of the 5-8 defect chain in graphene. 51,52 By arranging the pentagons, hexagons, and octagons, Mandal et al 31 and Sharma et al 30 recently reported two different 2D carbon allotropes composed of the 5-6-8 carbon rings, which are referred in this paper as the g-and 3-phographenes (accounting the pentagon-hexagon-octagon structural characteristics) to facilitate discussion. By carrying out the global minimum structure search with the efficient evolutionary algorithm, we have found three new structural isomers of the phographene, which would be discussed as the a-, b-, and dphographenes in this paper.…”
Section: Introductionmentioning
confidence: 90%
“…Theoretical studies predicted that α-, β-, and γ -graphynes are stable; while α-and β-graphynes preserve Dirac cones, γ -graphyne is a semiconductor due to the Kekule distortion effect [22,23]. Ram et al [24] predicted a sp 2 hybridized 2D allotrope of carbon, named pentahexoctite, * ethem.akturk@adu.edu.tr † ciraci@fen.bilkent.edu.tr with mechanical strength comparable to that of graphene. In addition, Zhang et al [25] predicted five atomically thin, free-standing germanium selenide (GeSe) polymorphs, which have high kinetic stability and energy band gaps in the visible region.…”
Section: Introductionmentioning
confidence: 99%
“…5 With the combination of sp-, sp 2 -, and sp 3 -hybridized carbon atoms, a number of 2D carbon materials with different architectures have also been synthesized and/or theoretically predicted. 2,[6][7][8][9][10][11][12][13][14][15][16][17][18] In particular, graphene has attracted major attention during the last decade, which also stimulated the studies of other 2D carbon materials such as γ-graphyne and graphdiyne ( Figure 1). 10,11,14,19,20 Atomically precise syntheses of γ-graphyne and graphdiyne remain elusive, but widely studied phenylene-ethynylene-based macrocycles can be regarded as their molecular subunits.…”
mentioning
confidence: 99%
“…Nevertheless, the number of reported examples of 2D carbon materials is still limited. 2,[6][7][8][9][10][11][12][13][14][15][16][17][18] By replacing ethynylene groups of γ-graphyne and graphdiyne with p-phenylene units, two purely sp 2 -hybridized 2D carbon structures with hexagonal symmetry can be conceived, which we name graphenylene-1 and graphenylene-2, respectively ( Figure 1). Notably, graphenylene-1 corresponds to a single-layer substructure of the hypothetical carbon allotrope "cubic graphite", 26 the synthesis of which still remains elusive.…”
mentioning
confidence: 99%